2013
DOI: 10.1097/iop.0b013e3182873d2e
|View full text |Cite
|
Sign up to set email alerts
|

CT Assessment of the Nasolacrimal Canal in a Black African Population

Abstract: The mean bony nasolacrimal canal diameter as measured by CT in Nigerians is smaller than those reported in African Americans, Asians, and Caucasians despite the reported lower prevalence of PANDO among blacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
0
20
3
Order By: Relevance
“…The measurements of the NLD bone in our study are smaller than reported in the literature in several populations, such as Asians and Africans (Saxena; Janssen et al; Shigeta et al;McCormick & Sloan;Fasina & Ogbole;Takahashi et al, 2011Takahashi et al, , 2013Yong et al) that showed greater diameters than those found in our population (Table III). Our study in Mexican population reports values that tend to be smaller than those of other populations, so we believe that there are differences in the NLD between ethnic groups (Table III), which could explain differences between countries in prevalence of lower nasolacrimal duct obstruction in adults.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The measurements of the NLD bone in our study are smaller than reported in the literature in several populations, such as Asians and Africans (Saxena; Janssen et al; Shigeta et al;McCormick & Sloan;Fasina & Ogbole;Takahashi et al, 2011Takahashi et al, , 2013Yong et al) that showed greater diameters than those found in our population (Table III). Our study in Mexican population reports values that tend to be smaller than those of other populations, so we believe that there are differences in the NLD between ethnic groups (Table III), which could explain differences between countries in prevalence of lower nasolacrimal duct obstruction in adults.…”
Section: Discussioncontrasting
confidence: 56%
“…Variations in the diameter of the NLD have been studied in bone specimens and by computerized tomography (CT) (Saxena, 1984;Groessl et al;Janssen et al;Shigeta et al;McCormick & Sloan, 2009;Fasina & Ogbole, 2013;Ramey et al, 2013;Takahashi et al, 2011Takahashi et al, , 2013Yong et al, 2014) Obstruction of the NLD can occur anywhere in its trajectory; however, previous studies with dacryocystography and dacryoendoscopy have determined that in two thirds of patients, the most common site of obstruction is the entrance to its bony portion (62-73 %), and this is not always considered in CT studies (Sasaki et al, 2005;Francisco et al, 2007). The morphology of the entrance to the NLD varies among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…13 In Nigerian population it was found to be 3.52 mm (± 0.69 mm) and 3.36 mm ( ± 0.64 mm) in male and female patients respectively by CT scans. 14 Janssen et al 15 by using axial CT measured NLD diameter to be 3.5 mm in the control group and 3.0 mm in the patient group (primary acquired nasolacrimal duct obstruction) which was significantly smaller than that in the control group and postulated that the smallest diameter of the bony canal is most relevant for ascertaining the origin of the obstruction of the lacrimal drainage system due to swelling of the mucosa. On the contrary McCormick and Sloan, 16 in a multiracial group study suggested that nasolacrimal canal diameter may not be a major factor for lacrimal drainage obstruction.…”
Section: Discussionmentioning
confidence: 97%
“…While not significant, patients overall had larger volumes than controls, which was also found by association in other studies. 9,10 In one, researchers found that Nigerians had smaller diameter canals than Caucasians and Asians even though they had a lower prevalence of PNLDO. 10 In the other, Pacific People had larger diameters than Caucasian and New Zealand Maori, despite a higher incidence of dacryocystorhinostomy.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,6,7,8 In other association studies, researchers have found that populations that tend to have a higher prevalence of PNLDO actually have larger minimum diameters, implying that a large diameter may be an effect rather than a cause of PNLDO. 9,10 The discrepancy is in part due to the difficultly making a two dimensional measurement of a three dimensional space since the minimum diameter varies depending on the plane of the image. Only one study has examined the three dimensional characteristics of the nasolacrimal duct in normal subjects, but found no difference in the diameter or volume between groups of varying age, gender, or race.…”
Section: Introductionmentioning
confidence: 99%